“‘From Our Lips:’ Lipstick as Consumer Technology and the MAC VIVA GLAM Advertising Campaigns” - Benoit, Andrea (Scientia Canadensis, 2013)
Lipstick has remained a stable technology for over five thousand years, while influenced by social and cultural mores, and ideas about sexuality, gender and class. This is particularly evident in the twentieth century since lipstick has become a consumer technology, as evidenced by the fundraising lipstick VIVA GLAM. Made by the originally Canadian brand MAC Cosmetics, sales of VIVA GLAM generate funds for the brand's own AIDS charity, the MAC AIDS Fund. VIVA GLAM’s advertising was initially controversial because it featured drag performer RuPaul in 1995 and Canadian crooner k. d. lang in 1997. More recently, VIVA GLAM’s advertising has featured singers Cyndi Lauper and Lady Gaga and promoted safe sex behaviours amongst young heterosexual women. Lipstick’s meaning and function continues to adapt to its historical circumstances, particularly around gender norms, and VIVA GLAM is a new chapter in this cultural history of lipstick as a consumer technology.